Enhancing the Focus of Peace Education in Spanish University Education: A Proposal of Activities in English Language Courses - Martínez-Lirola, María (Íkala, Revista de Lenguaje y Cultura, 2017)
This article proposes a pedagogical proposal based on peace education, in concrete in two subjects of English in the degree of English Studies. The purpose of the proposal is that students can acquire social competences such as communication, cooperation or the effective resolution of conflicts at the same time that they develop the different skills that are necessary in a foreign language subject (listening, speaking, reading, writing and interaction). Different activities based on social topics that gave importance to peace and justice were designed to carry out the study, Moreover, a survey was designed in order to know the opinion of University students on the activities and the methodology used. The results of the survey point out that students are aware that the pedagogical proposal based on peace education helps them to their integral development, to the acquisition of different competences and to improve their linguistic skills. The activities designed and the results of the survey are a clear example of a teaching-learning process that is not only based on learning contents but that it also highlights that the way students learn is based on competences so that students assume an active and committed role with society.